PENINGKATAN KEMAMPUAN KOMUNIKASI ANAK DISLEKSIA MELALUI TERAPI BAHASA SEDERHANA DI PANTI ASUHAN YAYASAN TUNA NETRA KARYA MURNI MEDAN - Liana, Liana; Manik , Wira; Pangaribuan, Jontra Jusat; Sagala , Sinta Afryanti; Barus , Dwita Dasya Br; Tarigan , Alexsa Febiola Br; Sari , Sopiah Maya (PUAN INDONESIA, 2025)
This service aims to describe the forms of dyslexia language disorders in the communication of children aged 7 to 12 years who live in the Yayasan Tuna Netra Karya Murni orphanage. Dyslexia is a learning disorder that affects children's reading, writing, and speaking abilities. In the context of an orphanage, children often do not receive adequate assistance, so that dyslexia symptoms are not optimally handled. This study uses a descriptive qualitative method with data collection techniques through observation and interviews with caregivers and children in the orphanage. The results showed that children aged 7–12 years with dyslexia had difficulty recognizing letters, often reversed sounds or the order of letters in words, experienced delays in responding to questions, and had difficulty constructing sentences coherently. In addition, some children showed disorders in pronunciation, understanding spoken language, and a tendency to withdraw from conversations. The level of disorder varies depending on the age and ability of the individual. Children aged 7–8 years showed more phonological disorders, while children aged 11–12 years had difficulty in conveying ideas verbally. This study concludes that dyslexia language disorders in children in orphanages require special treatment through speech therapy approaches, early intervention, and communication training that are appropriate to the characteristics of the age and needs of the children.